2018
DOI: 10.1002/2017ja024945
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Throat Aurora Being the Ionospheric Signature of Magnetopause Transient and Reflecting Localized Magnetopause Indentations

Abstract: Magnetopause transients, observing as brief entries into the magnetosheath by satellites, are commonly observed in the vicinity of the magnetopause and have been explained by several possible mechanisms. However, satellite observations alone are insufficient to determine the dynamics and context of transients. Throat auroras are characterized as north‐south aligned discrete auroral forms extending from the equatorward edge of the discrete auroral oval that are only observed near dayside convection throat regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
(69 reference statements)
2
23
0
Order By: Relevance
“…In addition, similar effects of the foreshock pressure pulses and magnetosheath jets in the magnetosphere were reported (e.g. Korotova et al, 2011;Hietala et al, 2012).…”
Section: Discussion and Summarysupporting
confidence: 75%
“…In addition, similar effects of the foreshock pressure pulses and magnetosheath jets in the magnetosphere were reported (e.g. Korotova et al, 2011;Hietala et al, 2012).…”
Section: Discussion and Summarysupporting
confidence: 75%
“…These deformations are supposed to be dented structures on the subsolar magnetopause. Later, Han et al () found one‐to‐one correspondences between throat auroras observed on the ground and magnetopause transients observed near the subsolar magnetopause, which have been suggested to be the direct evidence for throat auroras being the ionospheric signature of magnetopause indentations. In addition, it was found that the spatial scale of the magnetopause indentation can be as large as ~2.0 × 3.0 R E (Earth radius) after mapping a throat aurora to the geomagnetic equatorial plane, and the occurrence rates are as high as ~50% and ~25% counted by day and by 10 min, respectively (Han et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…whereas southward IMF has a weaker influence on its occurrence. Based on the comprehensive 613 study of properties of throat aurora, Han et al (2018) concluded that throat auroras are definite 614 ground signatures for local magnetopause deformations and compressions produced by 615 magnetosheath plasma jet impact. They also provided direct evidence that the source of 616…”
Section: Discussion and Summary 510mentioning
confidence: 99%